2005
DOI: 10.1002/ijc.21577
|View full text |Cite
|
Sign up to set email alerts
|

Diet and body mass, and oral and oropharyngeal squamous cell carcinomas: Analysis from the IARC multinational case–control study

Abstract: Tobacco and alcohol use are the main risk factors for oral and oropharyngeal cancers, yet, dietary habits may also be of importance. Data from a series of case-control studies conducted in 9 countries worldwide (1,670 cases and 1,732 controls) were used to investigate the role of several food groups and body mass index (BMI). Low BMI significantly increased the odds ratio (OR) of cancer more than 2-fold among ever-and never-tobacco users and ever-and never-alcohol drinkers. After adjustment for potential confo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
60
0
13

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 35 publications
9
60
0
13
Order By: Relevance
“…No entanto, os resultados dos estudos epidemiológicos são inconsistentes, e a avaliação da possível contribuição quantitativa para a diminuição do risco permanece incerta 7,12 . Nos estudos de Kjaerheim et al 6 , Franceschi et al 13 e Garrote et al 14 , as leguminosas associaram-se positivamente ao câncer, enquanto Petridou et al 15 , Kreimer et al 16 e De Stefani et al 17 observaram associação negativa para leguminosas. Nos estudos de Chyou et al 18 , Garrote et al 14 , De Stefani et al 17 , o consumo mais freqüen-te de arroz e massas associou-se com aumento do risco para o câncer oral.…”
Section: Discussionunclassified
See 3 more Smart Citations
“…No entanto, os resultados dos estudos epidemiológicos são inconsistentes, e a avaliação da possível contribuição quantitativa para a diminuição do risco permanece incerta 7,12 . Nos estudos de Kjaerheim et al 6 , Franceschi et al 13 e Garrote et al 14 , as leguminosas associaram-se positivamente ao câncer, enquanto Petridou et al 15 , Kreimer et al 16 e De Stefani et al 17 observaram associação negativa para leguminosas. Nos estudos de Chyou et al 18 , Garrote et al 14 , De Stefani et al 17 , o consumo mais freqüen-te de arroz e massas associou-se com aumento do risco para o câncer oral.…”
Section: Discussionunclassified
“…Tal achado deve ser recebido com cautela, devendo ser melhor investigado. Pode significar uma substituição das refeições estruturadas, em geral mais variadas e com maior aporte nutritivo, por bebidas lácteas e lanches, mais monótonas e com maior consumo de embutidos, em geral implicados como fatores de risco 13,16 .…”
Section: Discussionunclassified
See 2 more Smart Citations
“…General characteristics of case-control and cohort studies are shown in Tables 1 and 2, respectively. Case-control studies were published between 1994 and 2014; three were conducted in Italy (13,19,22) , two each in Iran (10,15) , China (12,23) and Australia (14,29) , and one each in Poland (16) , Spain (11) , Czech Republic (17) , Brazil (18) , UK (20) , India (24) , Hawaii (25) , Mexico (26) , Sweden (27) and Uruguay (28) . One was a multinational study conducted in nine countries worldwide (Italy, Spain, Poland, Northern Ireland, India, Cuba, Canada, Australia and Sudan) (21) Cohort studies were published between 1998 and 2012; nine were conducted in the USA (30,31,(34)(35)(36)(37)39,40,45) and eight were conducted in Europe (32,33,38,(41)(42)(43)(44)46) . Pooled analysis were conducted in the USA, Canada, Europe and Australia and included from seven to fourteen prospective studies (47)(48)(49)(50) .…”
Section: Literature Searchmentioning
confidence: 99%